Analisis Yuridis Sengketa Harta Bersama Pasca Perceraian dalam Putusan Mahkamah Agung No. 1996 K/Pdt/2012 - pangestu, Ramadhani dwi; Ambarwati, Mega Dewi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This paper analyzes the Supreme Court's decision Number 1996 K/Pdt/2012 regarding the post-divorce joint property dispute between Budi Santosa and Yenny Tjiamudjaja. Joint property or gono-gini problems are often a source of conflict in divorce, especially when there is no separation of property agreement. This study uses a normative legal method with a qualitative approach to court decisions and positive legal provisions, such as Article 35 paragraph (1) of the Marriage Law and Article 97 of the Compilation of Islamic Law. The results of the analysis show that the Supreme Court prioritizes the principles of in dubio pro matrimonio and substantive justice in determining the status of property as joint property, and rejects the Defendant's arguments that have not been legally proven. This decision emphasizes the importance of proving the origin of property in civil cases, while also providing an important precedent in family law regarding the division of assets after divorce.